2021
DOI: 10.1088/1755-1315/762/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in the coastal ecosystems of small islands and its conservation status

Abstract: Around 77% of Indonesian islands is small islands and Indonesia known as mega biodiversity center, but coastal biodiversity of small islands was not well documented. The objective of this study is to assess coastal biodiversity in small islands and its conservation status. The study indicated that small islands provide complex biodiversity ranging from ecosystem to species. Diversity index of mangrove: 1.4-1.8, seagrass: 1.5–1.9, coral: 1.7–2.3. Ecosystem condition in urban small island was poor and in rural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Several studies have also reported that Ambon Bay is home to fish, coral, shellfish, gastropods, barnacles, bivalvia, crabs, and echinoderms [5,18,19]. Suyadi et al (2021) found 25 species (16 genera, nine families) of crabs and 33 species (19 families) of molluscs in Ambon Bay, 16 species of echinoderm [5,16]. So that in the Ambon Bay area, we will also find these organisms larvae (meroplankton).…”
Section: Composition Of Meroplankton In Ambon Baymentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have also reported that Ambon Bay is home to fish, coral, shellfish, gastropods, barnacles, bivalvia, crabs, and echinoderms [5,18,19]. Suyadi et al (2021) found 25 species (16 genera, nine families) of crabs and 33 species (19 families) of molluscs in Ambon Bay, 16 species of echinoderm [5,16]. So that in the Ambon Bay area, we will also find these organisms larvae (meroplankton).…”
Section: Composition Of Meroplankton In Ambon Baymentioning
confidence: 90%
“…In addition, that ecosystem is also a place for nursery ground so that larvae (meroplankton) can be found in these waters. Several studies have also reported that Ambon Bay is home to fish, coral, shellfish, gastropods, barnacles, bivalvia, crabs, and echinoderms [5,18,19]. Suyadi et al (2021) found 25 species (16 genera, nine families) of crabs and 33 species (19 families) of molluscs in Ambon Bay, 16 species of echinoderm [5,16].…”
Section: Composition Of Meroplankton In Ambon Baymentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia yang termasuk ke dalam negara tropis diapit oleh Samudera Hindia dan Pasifik mengakibatkan Indonesia mempunyai keanekaragaman hayati yang melimpah (Suyadi dkk., 2021). Indonesia mempunyai 17.504 pulau, 77% diantaranya merupakan pulau-pulau kecil.…”
Section: Pendahuluanunclassified
“…Gastropods belong to the phylum of mollusks as one of the marine biotas with high species diversity and spread in various marine habitats (Sukawati et al 2018;Suyadi et al 2021). In general, gastropods play an important role ecologically and economically (Cumplido et al 2022).…”
Section: Introductionmentioning
confidence: 99%